Simulation of Adsorption kinetics of malachite green onto coffee residues - Zoubir, Benmaamar; Boutoumi, Houcine; Hamitouche, Houria; Benmaamar, Hafidha; Mazari, Samira.; Benmaamar, Abdelamek; Aggoun, Amele (Science des matériaux (Laboratoire LARHYSS); Vol. 7 (2016): Science des matériaux (Laboratoire LARHYSS) Octobre, 2016)
Abstract – In this work, coffee residues were used as a zero-cost adsorbent for the application of adsorption removal of malachite green dye from simulated aqueous solution. Coffee residues were characterized by the point of zero charge (Mass titration). The point of zero charge of coffee residues was 4.37. Adsorption kinetics of malachite green onto coffee residues were studied in a batch system. The effects of pH and contact time were examined. The malachite green maximum adsorption occurred at pH 6 and the lowest adsorption occurred at pH 2. The apparent equilibrium was reached after 240 min. Optimal experimental conditions were determined. In order to determine the best-fit-kinetic adsorption, the experimental data were analyzed using pseudo-first-order, pseudo-second-order, pseudo-third-order, Esquivel, and Elovich models. Linear regressive method and non-linear regressive method were used to obtain the relative parameters. The statistical functions were estimated to find the suitable method which fit better the experimental data. Both methods were suitable to obtain the parameters. The linear elovich(type 1 and 2)model was best to fit the equilibrium data. The present work showed that coffee residues can be used as a low cost adsorbent for the malachite green removal from water.  Keywords: coffee residues (CR), linear, non-linear regression, Adsorption kinetics, error estimation, regression coefficient (R )